Pengaruh Pembiayaan Mudharabah, Pembiayaan Musyarakah Dan Piutang Murabahah Terhadap Return on Assets (ROA) Dan Return on Equity (ROE) - Ajizah, Euis; Furniawan, Furniawan (Universitas Pendidikan Indonesia, 2022)
The purpose of this research is to know either partially or simultaneously, the effect of mudharabah financing, musyarakah financing, and murabahah receivables on Return on Assets and Return on Equity. The approach used in this study is a quantitative descriptive analysis approach, with secondary data obtained from the IDX for the Bank Syariah Mandiri (BSM) 2016-2018. To measure using multiple linear regression. The criteria for regression analysis are: t statistical test, f statistical test and the coefficient of determination (R2). The results of research from research reports that have been carried out for partial results of the variable Mudharabah Financing, Musharaka Financing and Murabahah Receivables on ROA and ROE do not have a significant effect. Meanwhile, based on the simultaneous results of Mudharabah Financing, Musharaka Financing and Murabahah Receivables on ROA have a significant effect. The same is the case with Mudharabah Financing, Musharaka Financing and Murabahah Receivables Against ROE which states that there is a significant effect.